You need to convert the summation in a product, and since only a summation of like trigonometric functions can be converted into a product, either, you convert `sin x` into `cos (pi/2 - x)` , or `cos x` in `sin(pi/2 - x)` , such that:

`sin x + cos x = sin x + sin(pi/2 - x)`

You should use the following identity, such that:

`sin a + sin b = 2 sin(a/2 + b/2)cos(a/2 - b/2)`

Reasoning by analogy, yields:

`sin x + sin(pi/2 - x) = 2 sin(x/2 + pi/4 - x/2)cos(x/2 - pi/4 + x/2)`

`sin x + sin(pi/2 - x) = 2 sin(pi/4)cos(x - pi/4)`

Replacing `sqrt2/2` for `sin(pi/4)` yields:

`sin x + sin(pi/2 - x) = 2*(sqrt2/2)*cos(x - pi/4)`

Reducing duplicate factors, yields:

`sin x + sin(pi/2 - x) = sqrt2*cos(x - pi/4)`

**Hence, converting the summation into a product, yields **`sin x + cos x = sqrt2*cos(x - pi/4).`